Use of Images in The Poetry of The School of the 8th Grade of Islam Al-Ihsan Pesanggrahan - Aji Juniarsyah Nabawi; Juli Yani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The research entitled The Use of Imagery in Students' Poetry aims to determine the use of imagery in students' poetry. This study used a qualitative approach and the content analysis method. The data used in this study are the findings and quotations in the lines and stanzas of the students' poems. Data collection techniques using documentation studies. The results showed that the researcher found that there were 46 imagery elements contained in a collection of students' poems, including 18 visual imagery, 4 auditory imagery, 3 tactile imagery, and 21 motion imagery.